Professional Trainee Teacher's Readiness to Use Cloud Technologies in Educational Process: The Role of Academic Motivation - Khmil Nataliia (Centre for Behaviour and Wellness Advocacy, 2017)
This article examines the role of motivation in the formation of professional trainee teacher's readiness to use cloud technologies. The author observes that, it is possible to define the exact characteristics of the motivational criteria, which is a part of the motivational-valuable component of professional trainee teacher's readiness to use cloud technologies. These unique characteristics may include; (1) trainee teachers' knowledge of the importance of the pedagogical potential of cloud technologies, (2) their understanding of the importance of using cloud services in the training of their students, and (3) self-improvement, self-educational activity, the desire to create, implement and expand new ideas on using cloud technologies in the educational process.